Evaluation on customer adoption process and brand positioning for Scientige Sdn Bhd in 2007 - Ahmad, Norhaidah (2007)
Scientige Sdn Bhd is a company that involve in the oil, gas and petrochemical industry and the company offer various products and services in the field. Since the company is still new in the market ( 2 years in the field), the company required to have strong brand positioning so that the client will see them as capable in doing business since business in oil and gas is tough and competition is really stiff. The objectives of the study are to identify the level Client Adoption Process for Scientige Sdn Bhd towards the products and services provided and also to identify the level of effectiveness for brand positioning that contribute to successful of Scientige Sdn.Bhd’s positioning. In this context, the Client Adoption Process is focus to five stages which are Awareness Stage, Interest Stage, Evaluation Stage, Trial Stage and Adoption Stage. For brand positioning factors, there are several factors being studied. The factors are Reputation, Product and Services Performance, Product and Client portfolio beside another one which is Network. Based on the study, the most important stage that being ranked by the Scientige’s clients is Evaluation stage. On the other hand, clients also agreed the most important brand positioning factors is Performance with the specific factors are trust, the reliability and quality of product and services in performance as well as in portfolio beside strong Customer Relationship Marketing. Based on the findings, some suggestions have been recommended to Scientige Sdn Bhd to come up with new strategies to enhance the company brand positioning in the mind of the clients.